Technical aspects of renovation of the 16thcentury roof truss - Nowogońska, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main causes of damage to wooden structures in historic buildings are the effects of weather conditions and related aging processes. In the case of the roof truss of a 16thcentury church in Lubów, the technical condition is additionally affected by leaking roof covering, damaged gutters, downpipes and flashings. Some elements of the wooden structure underwent biological corrosion, which lost its strength values.
Keywords: historic building; wooden structures; roof truss; technical condition; renovation; obiekt zabytkowy; konstrukcje drewniane; więźba dachowa; stan techniczny; remonty